The effects of muscle-tendon surgery on dynamic electromyographic patterns and muscle tone in children with cerebral palsy - Dreher, Thomas; Heitzmann, Daniel; Gantz, Simone; Maier, Michael Wolfgang; Braatz, Frank; Wolf, Sebastian Immanuel (Gait & posture, 2013)
During multilevel surgery, muscle-tendon lengthening (MTL) is commonly carried out in children with cerebral palsy. However, it is unclear if MTL also modifies increased muscle tone and if pathologic activation patterns are changed as an indirect effect of the biomechanical changes. Since investigations addressing this issue are limited, this study aimed at evaluating the effects of MTL on muscle tone and activation pattern. Forty-two children with spastic diplegia who were treated by MTL underwent standardized muscle tone testing (modified Ashworth and Tardieu test), dynamic EMG and three-dimensional gait analysis before, one and three years after MTL. For the evaluation of muscle activation patterns the norm-distance of dynamic EMG data was analyzed. Range of motion and joint alignment in clinical examination were found to be significantly improved one year after MTL. However, deterioration of these parameters was noted after three years. Muscle tone was significantly reduced one year postoperatively but showed an increase after three years. Joint kinematics were found significantly closer to reference data of age matched controls initially after surgery, but deteriorated until three years postoperatively. However, the EMG patterns of the muscles which were surgically addressed were found to be unchanged in either follow-up. These findings suggest that despite the influence of MTS on biomechanics and physiology (muscle tone reduction and improvements of joint mobility and gait pattern) MTS does not change abnormal patterns of muscle activation. Recurrence of increased muscle tone and deterioration of kinematic parameters three years after surgery may be attributed to these persistent pathologic activation patterns.